Reliability of motion phase identification for long-track speed skating using inertial measurement units - Iizuka, T.; Tomita, Y. (PeerJ, 2024)
Background Precise identification of motion phases in long-track speed skating is critical to characterize and optimize performance. This study aimed to estimate the intra- and inter-rater reliability of movement phase identification using inertial measurement units (IMUs) in long-track speed skating.